Nicotinamide phosphoribosyltransferase (NAMPT) activity is essential for survival of resting lymphocytes. Issue 2 (26th November 2013) - Pittelli, Maria; Cavone, Leonardo; Lapucci, Andrea; Oteri, Claudia; Felici, Roberta; Niccolai, Elena; Amedei, Amedeo; Chiarugi, Alberto
Abstract : NAD biosynthesis is emerging as a key regulator of immune cell functions. Accordingly, inhibitors of the NAD‐synthesizing enzyme nicotinamide phosphoribosyltransferase (NAMPT) have anti‐inflammatory effects, counteract hematological malignancies and are being tested in clinical trials. Still, their effect on different cell types still waits to be fully investigated. Here we show that the NAMPT inhibitor FK866 induces NAD depletion in various mouse organs but selectively causes dramatic atrophy of the spleen red pulp. Accordingly, in cultured mouse lymphocytes exposed to FK866, NAD contents drop to 50% of basal values within 2 days, a condition sufficient to prompt complete cell death. Cultures of human lymphocytes are more resistant to FK866 and sustain a 50% NAD reduction for 5 days before dying. Death of both cell types can be prevented by different NAD precursors, indicating critical NAD homeostasis in lymphocytes. Indeed, inhibition of the NAD‐consuming enzyme poly(ADP‐ribose) polimerase‐1 suffices to prevent FK866‐induced NAD depletion and death of both lymphocyte types. Poly(ADP‐ribose) polymerase‐1‐null lymphocytes also undergo lower NAD depletion and reduced cell death when exposed to the drug. At variance with other cell types, neither apoptosis nor autophagy are exclusively responsible for lymphocyte death by FK866, consistent with a general impairment of lymphocyte homeostasis following NAD depletion. Data demonstrate a unique sensitivity of resting lymphocytes to NAD‐depleting agents, providing new hints of relevance to lymphocyte biology and therapeutic interventions with NAMPT inhibitors.